2017
DOI: 10.1111/ctr.13013
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of computed tomography for detecting hepatic steatosis in donors for liver transplantation: A meta‐analysis

Abstract: Computed tomography shows high accuracy in detecting significant HS while poor accuracy in detecting the presence of HS in liver donors. Donors estimated to have significant HS by CT may avoid unnecessary liver biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Based on the above research results, we investigated the relationship between hepatic and pancreatic steatosis parameters measured by non-enhanced CT 15 . CT is also known to be correlated with liver biopsy for the detection of HS in many studies 16 . Since CT is one of the most highly correlated methods with liver and pancreas biopsies, CT was chosen as the reference radiological method in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above research results, we investigated the relationship between hepatic and pancreatic steatosis parameters measured by non-enhanced CT 15 . CT is also known to be correlated with liver biopsy for the detection of HS in many studies 16 . Since CT is one of the most highly correlated methods with liver and pancreas biopsies, CT was chosen as the reference radiological method in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of CT in measuring hepatosteatosis (HS) is more pronounced. CT has become an alternative method for liver biopsy in many transplantation centres due to its strength in the determination of HS in liver transplant donor candidates 16 . Despite the power of CT and many other radiological methods in the diagnosis of HS, liver biopsy is still considered the gold standard method in diagnosing NAFLD 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies evaluating the accuracy of CT yielded similar results. A meta-analysis comparing CT with liver biopsies in liver donors showed that CT had a sensitivity and specificity of 0.81 and 0.94, respectively, and that the accuracy of CT increased when fat infiltration was higher [30]. Similarly, CT had a lower concordance with liver biopsies than ultrasound [31].…”
Section: Main Findingsmentioning
confidence: 99%
“…Computed tomography (CT) is more widely available, easier to perform, and facilitates quantitative HS assessment based on the measurement of liver attenuation. ( 11‐13 )…”
mentioning
confidence: 99%
“…Computed tomography (CT) is more widely available, easier to perform, and facilitates quantitative HS assessment based on the measurement of liver attenuation. (11)(12)(13) Previous studies show that the distribution of fat within the liver is not uniform and that greater spatial heterogeneity exists in those with more severe HS. (14)(15)(16)(17) This nonuniform spatial distribution of fat may cause errors in quantification and classification of HS via liver biopsy, in which only a small piece of hepatic tissue is obtained.…”
mentioning
confidence: 99%